Prospective Study of BK Virus Infection and Nephropathy During the First Year After Kidney Transplantation (Iranian Journal of Kidney Diseases, 2014)
Introduction. The aim of this study was to assess the prevalence and severity of BK virus infection, BK virus nephritis, and related risk factors among kidney transplant recipients. Materials and Methods. BK viremia during the first year of kidney transplantation was assessed prospectively in 32 successive recipients. BK virus DNA was extracted and determined in all samples by real-time polymerase reaction assay for 1 year after kidney transplantation. Results. The mean age of the patients was 33.3 ± 15.3 years. Sixteen patients (50%) received antithymocyte globulin for induction therapy. Living donor transplant consisted of 75% of the kidney donations. Maintenance immunosuppressive therapy included cyclosporine A in 27 patients (84.4%), plus tapering prednisolone and mycophenolate mofetil. BK viremia was detected in 8 patients (25%). The highest detected plasma viral load was less than 4000 copies per milliliter. BK virus was respectively positive in 5 (62.5%), 2 (25%), and 1 (12.5%) patients during the first 4, 8, and 12 months after transplantation. Biopsy-proven rejection and antirejection therapy by methylprednisolone pulses were 5 and 2.3 times more common in patients with BK virus infection (P = .01 and P = .01), respectively. Conclusions. Despite occurrence of BK virus infection in 25% of our patients, BK nephropathy did not develop in any of them. Routine screening of BK virus infection, particularly in centers with low prevalence of BK virus nephritis, may not be cost effective for predicting this disease.